Potential of Wheat Straw, Spruce Sawdust, and Lignin as High Organic Carbon Soil Amendments to Improve Agricultural Nitrogen Retention Capacity: An Incubation Study - Reichel, Rüdiger; Wei, Jing; Islam, Muhammad S.; Schmid, Christoph; Wissel, Holger; Schröder, Peter; Schloter, Michael; Brüggemann, Nicolas (Frontiers in Plant Science, 2018)
Plants like winter wheat are known for their insufficient N uptake between sowing and the following growing season. Especially after N-rich crops like oilseed rape or field bean, nitrogen retention of the available soil N can be poor, and the risk of contamination of the hydrosphere with nitrate (NO3-) and the atmosphere with nitrous oxide (N2O) is high. Therefore, novel strategies are needed to preserve these unused N resources for subsequent agricultural production. High organic carbon soil amendments (HCA) like wheat straw promote microbial N immobilization by stimulating microbes to take up N from soil. In order to test the suitability of different HCA for immobilization of excess N, we conducted a laboratory incubation experiment with soil columns, each containing 8 kg of sandy loam of an agricultural Ap horizon. We created a scenario with high soil mineral N content by adding 150 kg NH4+-N ha-1 to soil that received either wheat straw, spruce sawdust or lignin at a rate of 4.5 t C ha-1, or no HCA as control. Wheat straw turned out to be suitable for fast immobilization of excess N in the form of microbial biomass N (up to 42 kg N ha-1), followed by sawdust. However, under the experimental conditions this effect weakened over a few weeks, finally ranging between 8 and 15 kg N ha-1 immobilized in microbial biomass in the spruce sawdust and wheat straw treatment, respectively. Pure lignin did not stimulate microbial N immobilization. We also revealed that N immobilization by the remaining straw and sawdust HCA material in the soil had a greater importance for storage of excess N (on average 24 kg N ha-1) than microbial N immobilization over the four months. N fertilization and HCA influenced the abundance of ammonia oxidizing bacteria and - archaea as the key players for nitrification, as well as the abundance of denitrifiers. Soil with spruce sawdust emitted more N2O compared to soil with wheat straw, which in relation released more CO2, resulting in a comparable overall global warming potential. However, this was counterbalanced by advantages like N immobilization and mitigation of potential NO3- losses.